O perfil do estudos sobre educação cooperativista e os rumos da discussão nas cooperativas agropecuárias nos últimos 5 anos. - Sousa,Sheilla Melo da Luz (Universidade Federal do Tocantins, 2023)
This work aims to understand the importance of cooperative education in agricultural cooperatives, considering that education is of fundamental importance for the development and also for the learning of cooperative members about the cooperative enterprise. In recent years, the importance of cooperative education in the agricultural sector and the influence of this education on the development of this sector has been discussed. Through the research, it was possible to use as a search string the word “Cooperative Education” + “Agricultural Cooperatives” in the following fields: title, abstract and keywords. The query resulted in 203 works in total, dating from the period between 2016 and June 2021. The next phase was to filter only articles, as the search also presented numerous theses and dissertations, in addition to works published in congress proceedings and some repetitions . With the filter, 16 works remained for the analysis, which resulted in the total of analyzed productions.